ECONOMIC NATIONALISM’S VIABILITY UNDER GLOBALIZATION - Elena Mihaela ILIESCU (Challenges of the Knowledge Society)
The path undertaken by the world economy is irreversible - the world economic system is a system based on interdependencies, cooperation and multilateralism but economic openness is not full. Each country, in order to protect their national interest call, in different proportion, depending on the circumstances and of the economic-social and political interests, for different forms of the economic nationalism, forms that have adapted continuously to the demands required for integrating on the foreign markets. The recent global economic crisis intensified the rhetoric and the economic nationalism’s practices but it is not about rebirth, but of renewal, of remodeling the nationalist policies, globalization being a premise of the new economic nationalism. The scope of this paper is to emphasize using empirical data the fact that nationalism and globalization, from an economical point of view, are not antagonistic policies, they coexist and influence each other, both generating contradictory effects, in terms of provided opportunities and risks.